[Ulica Długa, róg ul. Garbary, kamienice nr 4, 2/3 fot. Tadeusz Wański. - Wański, Tadeusz (1894-1958) (Tadeusz Wański HON EFIAP Art. Fotografik Z. P. A. F., 1953)
Przedstawia kamienice przy ul. Długiej nr 4 i 2/3 na rogu z ul. Garbary, ok. 1953 r.